How does heat stress affect sponge microbiomes? Structure and resilience of microbial communities of marine sponges from different habitats - De Castro-Fernández, Paula; Ballesté, Elisenda; Angulo-Preckler, Carlos; Biggs, Jason; Avila, Conxita; García-Aljaro, Cristina (Frontiers in Marine Science, 2023)
Sponges are key components of marine benthic communities, providing many ecosystem functions and establishing close relationships with microorganisms, conforming the holobiont. These symbiotic microbiotas seem to be host species-specific and highly diverse, playing key roles in their sponge host. The effects of elevated seawater temperature on sponges and their microbiota are still poorly known, and whether sponges from polar areas are more sensitive to these impacts respect to temperate and tropical species is totally unknown. We analyzed the microbiomes of different sponges and that of sponge samples exposed to heat stress experiments in aquaria by 16S rRNA amplicon sequencing to (1) characterize the sponge microbiota covering a latitudinal gradient (polar, temperate and tropical environments), and (2) asses the effects of thermal stress on their microbial communities. Bacterial communities’ structure was different in the different sponge species and also respect the surrounding seawater. The core microbiome is maintained in most sponges after a heat stress, although whether they would recover to the normal conditions previous to the stress remains yet to be further investigated. We observed increased abundances of transient bacteria from unknown origin in sponges exposed to heat stress. Some of these may be opportunistic bacteria that may benefit from the heat stress-associated dysregulation in the sponge by occupying new niches in the holobiont. According to our results, sponges from Antarctic waters could be more resilient than tropical and temperate sponges. Both the microbiome composition and the changes produced by the heat stress seem to be quite host species-specific, and thus, depend on the sponge species. Under a global change scenario, the microbiomes of the tropical and temperate sponges will probably be those suffering the most the heat stress, and therefore the effects of global change may be dramatic for benthic ecosystems since sponges are a fundamental part of them.